Implications of Language Politeness in Efforts to Prevent Westernization Behavior and Horizontal Conflict - Pratikno, Heru; Wulansari, Atsani; Purwanto, Kokok Dj (Wanastra: Jurnal Bahasa dan Sastra, 2025)
The purpose of this study is to find out the influence of foreign culture on the use of regional and national languages. In addition, this study was conducted to determine the role of language in preventing the horizontal conflicts in society that are emerging today. Data collection was carried out using the listening and note-taking method, the data was taken from documentation studies in online mass media. In analyzing the data, this study used a qualitative descriptive method. The results of the study show that it is so easy for the influence of Western culture and extreme understanding to enter the younger generation. The consistent use of polite language is a challenge for the younger generation to apply when interacting, both in society and on social media. For this reason, the role of family and community is very important in preventing Westernization and horizontal conflict, namely by prioritizing the use of good language.